PENGEMBANGAN PEMBELAJARAN LEMPAR CAKRAM MENGGUNAKAN PENDEKATAN BERMAIN - Amin, Jinnan Wahyudi; Kurniawan, Ari Wibowo (Gelanggang Pendidikan Jasmani Indonesia, 2024)
The aim of this development research is to develop a discus throwing learning model using a play approach for class VIII students at State Junior High School 1 Pademawu, Pamekasan Regency. The development method is based on a method consistent with that of Borg and Gall. The results from the athletic learning expert validation obtained an overall score of 121 or 94.5%, while the results from the media expert validation obtained an overall score of 110 or 91.7%. The assessment of small group trials obtained an overall score of 1503 or 89.46%, while the assessment of large group trials obtained an overall score of 3047 or 90.68%.